2008
DOI: 10.1111/j.1744-9987.2008.00564.x
|View full text |Cite
|
Sign up to set email alerts
|

Compositional and Oxidative Analysis in the Saliva and Serum of Predialysis Chronic Kidney Disease Patients and End‐stage Renal Failure Patients on Peritoneal Dialysis

Abstract: Chronic renal failure (CRF) is often treated with peritoneal dialysis, although increased oxidative stress has been reported in such patients. The purpose of the current study was to analyze and compare oxidative stress and other compositional parameters in the saliva, serum and peritoneal dialytic fluid (PDF) of patients with chronic kidney disease (CKD), including predialysis CKD patients and end-stage renal disease (ESRD) patients treated with peritoneal dialysis. Twenty-three consenting patients participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…Several studies have shown that while the same findings may be observed in PD patients as well, antioxidant levels are more favorable in HD group [26,27]. It has been showed that antioxidant levels of predialysis group, on the other hand, are lower than in the control group, but higher than in HD or PD group [5,27].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Several studies have shown that while the same findings may be observed in PD patients as well, antioxidant levels are more favorable in HD group [26,27]. It has been showed that antioxidant levels of predialysis group, on the other hand, are lower than in the control group, but higher than in HD or PD group [5,27].…”
Section: Discussionmentioning
confidence: 81%
“…In a multitude of studies, it has been found that in CRF, while MDA rises [20][21][22][23], antioxidant levels fall compared to the control group [24][25][26]. Several studies have shown that while the same findings may be observed in PD patients as well, antioxidant levels are more favorable in HD group [26,27]. It has been showed that antioxidant levels of predialysis group, on the other hand, are lower than in the control group, but higher than in HD or PD group [5,27].…”
Section: Discussionmentioning
confidence: 97%
“…Oxidative stress, defined as a rupture between prooxidant and antioxidant system that further leads to oxidative damage, has been observed in hemodialysis [5], peritoneal dialysis [6], as well as predialysis patients with chronic renal failure [7]. Additional literatures indicated that plasma antioxidant enzymes glutathione peroxidase (GPx), glutathione reductase (GR), and catalase activities decreased dramatically in patients undergoing hemodialysis [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…7,12 Saliva is a suitable body fluid for measurement of many enzymes, hormones, and other substances due to its easier availability, non-invasive nature, lower risk of blood diseases and infections, and the possibility of safely freezing and storage of samples. 13,14 On the other hand, as saliva is very similar to blood in terms of biochemical compounds, it is suggested that saliva may possess similar radicals scavenging ability as that of blood samples. 15,16 Strong correlation has been reported between plasma and salivary antioxidant changes in relation to physical activity.…”
Section: Introductionmentioning
confidence: 97%